Ergonomics applied to the inclusion of people with disabilities in the labor market - Scatolim, Roberta Lucas [UNESP]; Guarnetti dos Santos, Joao Eduardo [UNESP]; Landim, Paula da Cruz [UNESP]; Gomes de Moraes, Guilherme Aparecido [UNESP]; Arezes, P.; Baptista, J. S.; Barroso, M. P.; Carneiro, P.; Cordeiro, P.; Costa, N.; Melo, R.; Miguel, A. S.; et al. (Portuguese Soc Occupational Safety & Hygiene, 2015)
This study addresses aspects of the labor market and their suitability for the physically challenged, considering studies focused on thematic and compliance with laws and technical standards, enabling the inclusion of people with reduced mobility in work stations. The scientific approach sought through ergonomic studies to analyze the detection of problems for the issue of the difficulty of employment of people with disabilities into society, presenting some legal devices for protection and social inclusion and wheelchair accessibility in Brazil.
Keywords: disabled; ergonomics; labor market